Optimalni model koordinacije svetlobnih signalnih naprav v razcepnem diamantnem križišču na prometni mreži - Trček, Luka (Gradbeni vestnik, 2021)
This article presents an unconventional approach to traffic signal coordination on a road network with a diverging diamond interchange with traffic actuated signals. While this novel design can significantly improve the efficiency of an interchange, it introduces difficulties in coordinating with other traffic signals due to non-classical traffic signal operation, as the two main directions cannot be managed in the same phase.We compare different traffic signals coordination models in terms of increasing network capacity and reducing vehicle delays. Two different origin-destination matrices and four different coordination models were studied. We determined the optimal cycle length and theoptimal split for each coordination model and each origin-destination matrix and calculated three performance parameters, namely average delay, degree of saturation and stop rate. The results show different performances of the four coordination models, resulting insignificant differences in network capacities. Interestingly, higher network capacity does not necessarily lead to lower average delay in the network. Additionally, we have shown, that traffic signal coordination on a road network with diverge diamond interchange with the aim of reducing vehicle delays is beneficial when traffic volumes reach 80% of the capacity of uncoordinated road network. Finally, we determined a coordination model that is least sensitive to changes in origin-destination matrix to account for normal variations in traffic volumes.
Keywords: average delay; coordination; diverging diamond interchange; kapaciteta omrežja; koordinacija; network capacity; povprečna zamuda vozil; razcepno diamantno križišče